Usage of Social Stories in Encouraging Social Interaction of Children with Autism Spectrum Disorder - Sunitha Balakrishnan; Aliza Alias (Department of Special Education, 2017)
Social story is a very popular intervention and used widely as a social learning tool for children with autism spectrum disorder (ASD). The purpose of this research was to investigate the usage of social stories in encouraging social interaction of children with ASD. The subjects for this study were 4 learners with ASD between the ages of 5 to 8 who were attending school in an inclusive setting. A single case experiment with A-B-A-B design was used for all 4 subjects. Three of the subjects showed great improvement in their ability to make friends. Improvement was also seen in their communication based on visual obeservation to the targeted behavior chart whereas 1 subject only showed very little improvement. The findings of this study suggest that the usage of social stories in improving the social interaction of children with ASD has a positive impact.